PENGARUH PENERAPAN METODE INQUIRY TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS KELAS IV - Linarti, Linarti; Rosnita, Rosnita; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to analyze student learning outcomes that are taught by inquiry methods and taught by conventional methods in learning social science in class IV SDN 50 Pontianak Barat. The method used in this research is the experimental method. The form of research used was a quasi-experimental design with nonequivalent control group design. The study sample consisted of 58 students consisting of 30 students in grade IV C as the control group and 28 students in grade IV A as the experimental group selected by simple random sampling technique. Data collection tools used in this study are written tests in the form of multiple choices. Based on the results of data analysis obtained the average learning outcomes of control class 69.70 and the average learning outcomes of experimental class 80.46 obtained t count (4.69)> t table (2.307) with the effect size value of 1.14. This shows that there is an effect of the application of inquiry methods on student learning outcomes in learning Social Sciences in class IV SDN 50 Pontianak Barat.Â Keywords: Inquiry Method, Learning Outcomes, Quasi Experimental